(3GdgfOSI GdHTQjI h GdYdGbGJ GdYGeI (B:s (3gfOSI GdbHhd h GdQVG (B/s - (3GdOdjej, YHO GdQRGb eMeOs ((3YeGf(B: s (3OGQ hGFd(B, s, 2011)
(3eONd Gdi GdYdGbGJ GdYGeI GdbOjeI , GdYdGbGJ GdYGeI aj GdNGQWI GdJfXjejI ddeDSSI h eDSSh GdYdGbGJ GdYGeI , COhGQO HjQfjRh GdgfOSI GdHTQjI h Yde GdfaS h GdgfOSI GdHTQjI h GdOYGjI h GdbjGOI GdSjGSjI h LeYjGJ h efXeGJ GdYdGbGJ GdYGeI , CHQR TQcGJ GdYdGbGJ GdYGeI h GdYdGbGJ GdYGeI h GTcGdjGJ GdeUWdMGJ , GdgfOSI GdHTQjI h GdSdhc GdGfSGfj h GdYdGbGJ GdYGeI h LOd eQLYjJgGs
Keywords: (3GdGQZhfhejGs; (3GdYdGbGJ GdYGeIs; (3GdgfOSI GdHTQjIs